Relação entre hormônio antimülleriano, contagem de folículos antrais, volume ovariano e resultados de fertilização in vitro - Boeno, Andrey Cechin (2012)
The aim of this study was to check if there is a predictive relationship of measured serum levels of anti-Mullerian hormone (AMH), antral follicle count (AFC) and ovarian volume with the results of IVF. We conducted a prospective study between January 2010 and March 2012 with women aged 35 or more who underwent IVF. The levels of AMH, AFC and ovarian volume were correlated with response to ovarian hyperstimulation, with rates of fertilization, with embryo quality and pregnancy rates. We evaluated 40 patients with a median age of 39 years old. There was a significant direct correlation between the levels of AMH and the number of follicles larger than 14 mm (rS = 0.81 and P < 0.001). The same happened to the AFC (rS = 0.69 and P < 0.001). This correlation was not significant when evaluated the ovarian volume. AMH, AFC and ovarian volume did not show a statistically significant correlation with rates of fertilization, with embryo quality or with pregnancy rates. In predicting good or poor response, AMH and AFC showed a high positive predictive value (100% for the AMH and 87% for AFC, using a cutoff of 0.9 ng/ml and 7 follicles respectively, values established by ROC curve). We conclude from this study that AMH and AFC can be used as predictors of response to ovarian hyperstimulation in IVF, but they are not related to embryo quality, fertilization rates or pregnancy.